2023
DOI: 10.1007/s11547-023-01633-6
|View full text |Cite
|
Sign up to set email alerts
|

Prospective validation of 18F-Fluoroethylcholine as a tracer in PET/MRI for the evaluation of breast lesions and prediction of lymph node status

Abstract: Purpose To assess 18F-Fluoroethylcholine (18F-FEC) as a PET/MRI tracer in the evaluation of breast lesions, breast cancer aggressiveness, and prediction of lymph node status. Materials and methods This prospective, monocentric study was approved by the ethics committee and patients gave written, informed consent. This clinical trial was registered in the EudraCT database (Number 2017-003089-29). Women who presented with suspicious breast lesions were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Elevated SUV(maxLN) values were associated with metastatic lymph nodes, showing ROC values of 0.761 and 0.793 for SUV(maxT) and SUV(maxLN), respectively. The study concluded that simultaneous [ 18 F]FEC PET/MRI is safe and holds promise for assessing breast cancer aggressiveness and predicting lymph node status [ 123 ].…”
Section: Resultsmentioning
confidence: 99%
“…Elevated SUV(maxLN) values were associated with metastatic lymph nodes, showing ROC values of 0.761 and 0.793 for SUV(maxT) and SUV(maxLN), respectively. The study concluded that simultaneous [ 18 F]FEC PET/MRI is safe and holds promise for assessing breast cancer aggressiveness and predicting lymph node status [ 123 ].…”
Section: Resultsmentioning
confidence: 99%